Analisis Model Mundell-Fleming: Implikasi Kebijakan Fiskal dan Moneter dalam Sistem Ekonomi Terbuka - Maulana Azmi; Rida Rahma Yunita; Sarpini Sarpini (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
Globalization and economic openness have encouraged the integration of financial markets, which contributes to the smooth flow of capital between countries. This capital inflow provides various benefits, such as increased investment, technology transfer, and development of domestic financial markets. However, on the other hand, this also creates challenges in maintaining economic stability. In this context, monetary policy plays a very important role in achieving macroeconomic balance, through controlling inflation, price stability and exchange rates. Currently, global monetary policy's focus on inflation targeting is often criticized because of the trade-off with economic growth, which can be illustrated by the Phillips curve. The Mundell-Fleming model or IS-LM-BP, designed to analyze open economies, provides a useful framework for understanding the effectiveness of fiscal and monetary policies in maintaining internal and external balance. This model also considers capital movements between countries, thereby offering valuable insights for managing economic policy in the era of globalization.